Examining occupational fraud risk elements : evidence from the banking industry in Malaysia / Marzlin Marzuki … [et al.] - Marzuki, Marzlin; Mohd Jamil, Muslimah; Azizan, Siti Sakinah; Ismail, Tarmizi (Universiti Teknologi Mara Cawangan Pulau Pinang, 2024)
The present state of the global economy justifies discussions about occupational fraud. According to PricewaterhouseCoopers's 2020 study, there is still a high incidence of fraud in Malaysia, 68% of which is committed by employees, and 35% of which is committed through external collusion. Asset misappropriation, bribery and corruption, customer fraud, and cybercrime are the top four disruptive fraud events Malaysian organisations have encountered in the past two years. Thus, financial organisations are thought to be more susceptible to fraud since they deal with large sums of cash on a regular basis. The purpose of this paper is to determine the risk elements on the occurrence of occupational fraud in the Malaysian banking industry. The Fraud Diamond Theory (Wolfe & Hermanson, 2004) is applied as the theoretical foundation for the research. Using data from a questionnaire survey of 94 employees of Malaysia's top three banks, multiple regression is used in this study to examine the relationships between the various hypotheses. The findings of this study reported that pressure, opportunity, and rationalisation were the main factors in occupational fraud occurrence in Malaysian financial institutions. This suggests that only these three elements of the Fraud Diamond Theory have a significant impact on the likelihood of occupational fraud. The implications of this research are for policy makers, industry players and consumers.